2005
DOI: 10.1002/bit.20555
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic model of quantitative real‐time polymerase chain reaction

Abstract: Real-time polymerase chain reaction (PCR) is one of the most sensitive and accurate methods for quantifying transcript levels especially for those expressed at low abundance. The selective amplification of target DNA over multiple cycles allows its initial concentration to be determined. The amplification rate is a complex interplay of the operating conditions, initial reactant concentrations, and reaction rate constants. Experimentally, the compounded effect of all factors is quantified in terms of an effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Long-range molecular correlations in the chemistry of DNA-enzyme interactions, discussed in Ref. [1], appear to play a key role in understanding how to reconcile the high efficiency and precise targeting of enzymatic catalytic activity with the intrinsically stochastic kinematics of a large number of molecular components [12][13][14]. The highly ordered pattern in the spatial molecular arrangements and the time ordered sequence of steps characterizing the catalytic activity indicate that biochemical methods and the traditional study of the dipole and multipole dynamical structure of the electronic quantum conformations, out of which the chemical properties of interacting molecules emerge, need to be supplemented by results in quantum field theory (QFT).…”
Section: Introductionmentioning
confidence: 99%
“…Long-range molecular correlations in the chemistry of DNA-enzyme interactions, discussed in Ref. [1], appear to play a key role in understanding how to reconcile the high efficiency and precise targeting of enzymatic catalytic activity with the intrinsically stochastic kinematics of a large number of molecular components [12][13][14]. The highly ordered pattern in the spatial molecular arrangements and the time ordered sequence of steps characterizing the catalytic activity indicate that biochemical methods and the traditional study of the dipole and multipole dynamical structure of the electronic quantum conformations, out of which the chemical properties of interacting molecules emerge, need to be supplemented by results in quantum field theory (QFT).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic model of quantitative real-time PCR for normal DNA sequences has been well-documented (Gevertz et al, 2005;Mehra and Hu, 2005). Hence, additional studies are needed to elucidate the kinetic mechanism of amplification of GC-rich templates.…”
Section: Discussionmentioning
confidence: 99%
“…The most general control system is based on the sequenceand temperature-dependent state space model for DNA amplification described above. Other control systems are based on simplified PCR models previously proposed in the literature [22][23][24][25] and correspond to approximations to the model described in Section II. For these latter models, we only consider the previously developed model structures with rate constants estimated based on the above approach, since Marimuthu et al 14 have shown that the rate constants that were used in the previously proposed models are thermodynamically inconsistent.…”
Section: Dynamic Models and Control Systems For Dna Amplificationmentioning
confidence: 99%
“…The state equations of the melting, annealing, and extension reactions were solved independently. Also, the rate constants of the respective reactions were held constant 22 . We call this kind of PCR model a 'Staged' or 'On-Off' time invariant DNA amplification model, since the control vector fields are assumed to be either turned on or off at each step of a PCR cycle.…”
Section: Mehra and Humentioning
confidence: 99%